1989
DOI: 10.1159/000120447
|View full text |Cite
|
Sign up to set email alerts
|

Ependymomas in Two Sisters and a Maternal Male Cousin with Mosaicism with Monosomy 22 in Tumour

Abstract: A family with two sisters and their mother’s male cousin had ependymomas. Of note is the fact that chromosome analysis on the tumour of the younger sister showed two cell lines, one a normal female line, the other with monosomy of chromosome 22.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Absence of disease in earlier generations has also been documented for other (sub)ependymoma families (Honan et al, 1987;Savard and Gilchrist, 1989). These family data suggest multifactorial inheritance in which ependymoma development is determined by two or more loci.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Absence of disease in earlier generations has also been documented for other (sub)ependymoma families (Honan et al, 1987;Savard and Gilchrist, 1989). These family data suggest multifactorial inheritance in which ependymoma development is determined by two or more loci.…”
Section: Discussionsupporting
confidence: 56%
“…Honan et al (1987) reported on a family of 11 siblings, of when five developed brain tumours: three had a subependymoma, one an ependymoma and one a brain tumour of unknown patholog y. In another famil y, two sisters and their mothe r's male cousin all developed an ependymoma (Savard and Gilchrist, 1989). One of the sisters had monosomy 22 in the tumou r. Ryken et al (1994) presented in their study a father and son, who both developed a subependymoma.…”
mentioning
confidence: 99%
“…52 Cytogenetic evidence for a chrom osom e 22 tum our suppressor gene in ependym om a was found by W erem owicz et al 53 N ijssen et al 54 reported a fam ily with anaplastic ependym om as. T hey found evidence of loss of chrom osom e 22 in tum our cells, which was also found by Savard et al, 55 Rogatto et al, 56 and Ransom et al 57 Slavc et al 58 concluded that a locus distinct from the locus of the N F 2-gene on chrom osom e 22 m ight be responsible for tum our genesis. G enetically, ependym om as m ay be considered as belonging to the group of low-grade gliom as.…”
Section: Genetic Changessupporting
confidence: 68%
“…The cousin's tumor was not available for review. Notably, these 3 "ependymomas" were previously reported [19].…”
Section: Resultsmentioning
confidence: 86%